DISCREPANCIES OF SKILLS ACQUIRED DURING TEACHER TRAINING PROGRAMME AND REQUIRED IN ACTUAL CLASSROOM - Tahseen Akhter, Aisha Akbar (PJE, 2023)
The improvement of a teacher’s education is a critical national necessity. The quality of teachers, more than any other factor, depends upon the quality of instructions, and, quality of instructions is largely determined by the excellence of the teachers. This requires that the teacher’s education institutions should be well equipped with human as well as physical facilities.